The use of English thematic module in enhancing student's writing skills in English / Mohd Lutfi Mat Amin - Mat Amin, Mohd Lutfi (2012)
This study investigated the use of English Thematic Module as one of the teaching strategies that have been suggested to be an effective method which could help students improve their English writing performance. This study is mainly focused on the level two students and as_. many as 27 of them were chosen through purposive sample of method for this case study. They were preparing themselves for their UPSR examination. Their performance was based on their last year's final year examination results. Take Off Value test (TOV) and Operational Target Incremental l(OTI I). They were observed for three years from 2008 until 2011. All data obtained from the questionnaires and interviews were analyzed respectively. This study was also implemented to assist primary school teachers get a clear picture on how effective cooperative learning strategy can be used as a teaching method in an English Language classroom. The instrumentation used was questionnaires, which was given to both selected teachers and students to explore their sensitivity towards the use of English Thematic Module as an effective teaching method in the classroom. Generally, via the findings, it is concluded that most of the samples showed their positive attitude and perceptions towards the use of English Thematic Module and they had come to an agreement of supporting the program as well. The findings suggest that the use of English thematic module is a relevant and applicable writing program that could be organized in the classroom in order to improve students’ writing skills.